Time-series analysis of the association between air pollution exposure and outpatient visits for dry eye disease: a case study in Zhengzhou, China - Xia, Mengting; Yang, Yingrui; Sun, Jiali; Huang, Ranran; Huang, Yonghui; Zhang, Mengqi; Yao, Xi (Frontiers in Public Health, 2024)
Background: Dry eye disease (DED) is a prevalent ocular surface disease that significantly impacts patients' quality of life. The association between air pollution and the risk of dry eye disease remains uncertain.Methods: Data on outdoor air pollutants, meteorological information, and outpatient visits for DED were collected from July 1, 2014, to December 31, 2019. The relationship between ambient air pollutants and DED outpatient visits was analyzed using a generalized additive model with a Poisson distribution.Results: Among the 5204 DED patients included in the study, 63.76% were female and 36.24% were male. The single-pollutant model revealed a significant association between a 10 μg/m3 increase in concentrations of fine-particulate matter with a median aerometric diameter of less than 10 μm (PM 10 ), sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), and carbon monoxide (CO) and outpatient visits for DED. Fine-particulate matter with a median aerometric diameter of less than 2.5 μm (PM2.5) showed a significant association with DED outpatient visits in males and the 19-59 years age group. The strongest associations between air pollutants and outpatient visits were observed in male patients and during the cold season.The noteworthy correlation between air pollutants and DED outpatient visits can offer evidence for policy makers and underscore the significance of reinforcing environmental protection.